PERANCANGAN BUKU POP-UP RELIEF FABEL CANDI SOJIWAN SEBAGAI MEDIA BELAJAR MELUKIS ANAK USIA DINI - Muryasari, Desiana; Putra, Ambar Aditya; Yusuf, Andi Wahyu Zulkifli (Narada : Jurnal Desain dan Seni, 2023)
The current study used a research and development approach to create a pop-up book media. It was fable reliefs from the Sojiwan Temple. This media was intended as a pedagogical tool for children's painting education. The study involved 30 kindergarten students from Laboratori Pedagogia FIP UNY. The focal point of investigation was the fable relief found at the Sojiwan Temple. Data analysis used the Miles and Huberman model, encompassing data reduction, data presentation, and drawing conclusions. The qualitative data analysis were transformed into pop-up media using the Borg and Gall model. It included needs analysis, information gathering, planning, initial product design, design validation, design revision, limited trials, product refinement, extensive testing, final product revision, and production stages. Based on the characteristics of young children, this pop-up book was "The Two Geese Flying the Tortoise." The result of this design effort was a portrait-oriented pop-up book, measuring 21x29.7cm, spanning 10 pages. This book features a combination of pop-up techniques, including pyramid, internal stand, v-folding, lift the flaps, quadrilaterals, pop-up house, solid shapes, zig-zag-fold, and the basic box. In summary, the pop-up book included an educational value sheet, imparting sagacious messages or advice while considering visual aspects. Furthermore, the expert judgment confirmed that the product's efficacy at 96.53% as "Highly Suitable" for painting education activities. In  other hand, individual painting result showcase that 53% of students is Developing Excellently," while 47% is "Developing as Expected." Finally, the pop-up book media featuring fable reliefs from the Sojiwan Temple had the potential to enhance painting education.